2018
DOI: 10.1177/0002716217743935
|View full text |Cite
|
Sign up to set email alerts
|

Out of West Africa: Human Smuggling as a Social Enterprise

Abstract: Drawing on 18 months of ethnographic research in Senegal, this article focuses on the sociality of migrant facilitation. Although it has become relatively common in media and policy reports to suggest that irregular migrants are manipulated by greedy and unscrupulous human smugglers, this article shows how migrants in Senegal are often familiar with their handlers and are more likely to call them a friend ( ami) than a criminal. Also, most migrants do not see themselves as “smuggled,” which implies victimhood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…Family members in the origin country who depend on their income, may pressure migrant workers, creating an imperative to work and avoid losing their job [15]. Furthermore, due to increasing migration restrictions, migrants may take increasingly dangerous and more costly migration routes, arriving with debts to be repaid [31]. While dependency on migrant smuggling does not apply to regular migrants, scholars have noted that the fees recruitment agencies charge can create similar effects [52].…”
Section: Points Of Vulnerability To Labour Trafficking Related To Migmentioning
confidence: 99%
“…Family members in the origin country who depend on their income, may pressure migrant workers, creating an imperative to work and avoid losing their job [15]. Furthermore, due to increasing migration restrictions, migrants may take increasingly dangerous and more costly migration routes, arriving with debts to be repaid [31]. While dependency on migrant smuggling does not apply to regular migrants, scholars have noted that the fees recruitment agencies charge can create similar effects [52].…”
Section: Points Of Vulnerability To Labour Trafficking Related To Migmentioning
confidence: 99%
“…Our analysis complements work on border enforcement by establishing ways that the transit environment drives migrant flows. Our work also complements qualitative research on transit and the importance of reputation and relational contracting within smuggling markets [5,15,16].…”
Section: Introductionmentioning
confidence: 82%
“…Economic theory provides a rationale for why smugglers have long term incentives to get their migrants into Europe. Specifically, Mediterranean human smuggling is built on repeated interactions [ 15 ]. With repeated interactions smugglers and intermediaries build reputations similar to firms with relational contracts in supply chains [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have observed similar dynamics in Africa (e.g. Ayalew Mengiste 2018;Brachet 2018;Maher 2018), the Americas (e.g. Gonzalez 2018;Sanchez 2014;Stone-Cadena and Álvarez Velasco 2018;Vogt 2016), Asia (e.g.…”
Section: Introductionmentioning
confidence: 86%